Atherosclerosis is aggravated by iron overload and ameliorated by dietary and pharmacological iron restriction - Vinchi, Francesca; Simmelbauer, Andreas; Altamura, Sandro; Spaich, Sebastian; Seide, Svenja; Sparla, Richard; Hentze, Matthias W.; Muckenthaler, Martina (European heart journal, 2020)
Whether and how iron affects the progression of atherosclerosis remains highly debated. Here, we investigate susceptibility to atherosclerosis in